Method for preparing exterior wall external thermal insulation foamed ceramic from graphite tailings
Through ball milling and dry molding and firing of graphite tailings and other raw materials, the problems of high thermal conductivity and low compressive strength of external insulation foam ceramics are solved, and efficient insulation performance improvement and graphite tailings resource utilization are achieved. Important economic and environmental benefits.
Patent Information
- Application Number
- CN202411282463.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-12
- Publication Date
- 2024-12-17
AI Technical Summary
The existing exterior wall insulation foam ceramics have a high thermal conductivity and low compressive strength. Due to the high calcium content of graphite tailings, it is impossible to achieve its high value-added application in foamed ceramics.
Using graphite tailings, coal gangue, potassium feldspar, gas induction agent, water reducing agent, talc and CaCO3 in proportion, it is made by dry molding and foaming, and has improved insulation performance and compressive strength. External insulation foam ceramic.
It effectively improves the insulation properties and compressive strength of external insulation foam ceramics, realizes the resource utilization of graphite tailings, has economic and environmental benefits, and meets the requirements of thermal insulation materials of relevant standards.
Smart Images

Figure CN119143474A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of foam ceramic preparation, in particular to a method for preparing exterior wall external thermal insulation foam ceramic by utilizing graphite tailings. Background Art
[0002] Foam ceramics are mainly used in the fields of construction, ships, power systems, industrial systems, cold storage, etc. In the field of construction, foam ceramics can be used in roofs, exterior walls, floors and other parts to improve the thermal insulation performance of buildings; currently, the external wall insulation foam ceramics have shortcomings such as high thermal conductivity and low compressive strength, and the performance of external wall insulation ceramics needs to be improved in a targeted manner; some studies have utilized graphite tailings, but the comprehensive utilization level is still low. Furthermore, due to the high calcium content of graphite tailings and other problems, it is impossible to achieve high value-added applications of graphite tailings in foam ceramics.
[0003] Therefore, a method for preparing exterior wall thermal insulation foam ceramics using graphite tailings is proposed to solve this problem. Summary of the invention
[0004] To achieve the above object, the present invention provides the following technical solution: a method for preparing exterior wall thermal insulation foam ceramics using graphite tailings, comprising the following steps:
[0005] Step 1: ball milling and mixing: graphite tailings, coal gangue, potassium feldspar, air entraining agent, water reducing agent, talc and foaming agent are weighed in proportion with CaCO3, and ball milled to obtain a mixture;
[0006] Step 2: blank preparation: the mixed material is dried at 110℃±5℃, and then dry-milled to obtain each test powder;
[0007] Step 3: Blank forming: using dry forming method, the obtained powder is pressed into shape;
[0008] Step 4: Firing and foaming: Place in a muffle furnace and sinter at 950°C.
[0009] Preferably, in step 1, the mixture obtained by ball milling is put into a ball milling jar in a ratio of material: ball = 1:2, material: water = 1:0.7, and wet ball milling is performed for 2 hours to obtain the mixture.
[0010] Preferably, in step 1, the mass fractions of the raw materials include: 35-40 parts of graphite tailings, 40-48 parts of coal gangue, 10 parts of potassium feldspar, 1-5 parts of air entraining agent, 1-5 parts of water reducing agent, 5-10 parts of talc and 10%-30% of CaCO3.
[0011] Preferably, in step 1, dry ball mill is used for dry ball milling.
[0012] Preferably, before the dry ball mill is put into operation, it is necessary to check whether all parts of the equipment are operating normally to ensure that there is no abnormality or failure in the equipment. After the dry ball mill is finished working, the unloading operation can only be carried out after the equipment is completely stopped. It is strictly forbidden to unload the dry ball mill when it is in working state.
[0013] Preferably, in step 2, the blank is prepared by dry ball milling for 1 hour, and the obtained powder is passed through a 100-mesh sieve.
[0014] Preferably, after the powder is sieved, the powder larger than 100 mesh is dry-milled again until it meets the sieving requirements.
[0015] Preferably, in step 3, the blank is formed by using a tablet press to press the obtained powder into a blank with a diameter of 3 cm at a pressure of 10-20 MPa.
[0016] Preferably, in step 3, the green body needs to be protected after being pressed into shape to prevent the green body from being hit, broken or crushed.
[0017] Preferably, in step 4, the sintering system is: first, heat to 700°C at a rate of 5°C / min, open the furnace door and quickly place the green body into the muffle furnace, then heat to 950°C at a rate of 4-5°C / min and keep warm for 60 minutes; after sintering is completed, the sample is cooled to room temperature with the furnace.
[0018] Compared with the prior art, the present invention has the following beneficial effects:
[0019] In view of the huge economic, social and environmental benefits of resource utilization of graphite tailings, the present invention can effectively improve environmental pollution problems and has extremely broad application prospects. The preparation of exterior wall thermal insulation foam ceramics using graphite tailings as the main raw material can not only provide a new way for the utilization of graphite tailings, but also provide a feasible solution for the preparation of exterior wall thermal insulation foam ceramics using solid waste. At the same time, the use of minerals such as graphite and quartz in the graphite tailings can also improve the thermal insulation and compressive strength of the exterior wall thermal insulation foam ceramics. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 is a preparation flow chart of the present invention;
[0021] Figure 2 Schematic diagram of XRD diffraction of the raw material of the present invention;
[0022] Figure 3 This is a sample diagram of an embodiment of the present invention. DETAILED DESCRIPTION
[0023] The present invention will be described in more detail below by way of examples, which are merely illustrative and do not in any way limit the scope of the present invention.
[0024] The present invention provides a technical solution: a method for preparing exterior wall thermal insulation foam ceramics using graphite tailings, comprising the following steps:
[0025] Step 1: Ball milling and mixing: Weigh the graphite tailings, coal gangue, potassium feldspar, air entraining agent, water reducer, talc and foaming agent with CaCO3 in proportion. The mass fraction of each raw material includes: 35-40 parts of graphite tailings, 40-48 parts of coal gangue, 10 parts of potassium feldspar, 1-5 parts of air entraining agent, 1-5 parts of water reducer, 5-10 parts of talc and 10%-30% of CaCO3, and ball mill to obtain a mixture; the mixture obtained by ball milling is put into a ball milling jar in the ratio of material: ball = 1:2, material: water = 1:0.7, and wet ball milling is performed for 2 hours to obtain a mixture; dry ball milling uses a dry ball mill; before the dry ball mill is operated, it is necessary to check whether all parts of the equipment are operating normally to ensure that there is no abnormality or failure of the equipment. After the dry ball mill is completed, the unloading operation can only be carried out after the equipment is completely stopped. It is strictly forbidden to unload when the dry ball mill is in working state;
[0026] Graphite tailings refer to waste generated during the mining process of graphite mines. The main components are minerals such as graphite and quartz. The graphite in graphite tailings has good thermal conductivity and can effectively reduce heat transfer. The addition of graphite in thermal insulation ceramics will further improve the thermal insulation performance of thermal insulation ceramics, making them have better thermal insulation effect. At the same time, quartz can play a role in strengthening ceramics. The addition of quartz minerals in graphite tailings will increase the hardness and compressive strength of ceramics. Quartz has lower thermal conductivity and higher thermal stability, which can reduce the thermal conductivity of ceramic products, reduce heat loss, and increase the thermal insulation effect of ceramics.
[0027] CaCO3 (calcium carbonate) controls porosity and shrinkage. During the ceramic manufacturing process, calcium carbonate can form carbon dioxide and calcium oxide through decomposition reaction. Calcium oxide can react with raw materials such as clay to form new compounds, thereby controlling the porosity and shrinkage in the green body. When calcium carbonate decomposes, the released carbon dioxide gas can fill the voids in the green body, improve the density of the green body, reduce the shrinkage of the green body at high temperature, and ensure the overall stability and quality of the ceramic products.
[0028] Calcium carbonate is added to ceramic blanks as a raw material to increase the compactness and hardness of the blank. When calcium carbonate reacts with raw materials such as clay, calcium ions can replace aluminum ions and silicon ions in the clay, making the crystal composition of the new substance denser. With high-temperature firing, the new substance undergoes a crystal phase change, forming a more solid ceramic.
[0029] The smoothness and uniformity of the ceramic surface are also affected by calcium carbonate. The carbon dioxide gas produced when calcium carbonate decomposes can fill the voids in the body and be evenly distributed throughout the body, making the surface of the ceramic body smoother and more delicate during molding. It is also beneficial to improve the smoothness and uniformity of the surface after firing.
[0030] Step 2: blank preparation: the mixed material is dried at 110℃±5℃, and then dry-milled to obtain each test powder; the blank preparation is dry-milled for 1h, and the obtained powder is sieved through a 100-mesh sieve; after the powder is sieved, the powder larger than the 100-mesh sieve is dry-milled again until it meets the sieving requirements;
[0031] Step 3: Blank forming: The obtained powder is pressed into a shape by a dry forming method; the blank forming is to use a tablet press to press the obtained powder into a blank with a diameter of 3 cm at a pressure of 10-20 MPa; after the blank is pressed and formed, the blank needs to be protected to avoid collision, breakage, and crushing of the blank;
[0032] Step 4: Firing and foaming: Place in a muffle furnace and sinter at 950°C; the firing system is: first heat up to 700°C at a rate of 5°C / min, open the furnace door and quickly place the green body into the muffle furnace, then heat up to 950°C at a rate of 4-5°C / min and keep warm for 60 minutes; after sintering is completed, the sample is cooled to room temperature with the furnace.
[0033] Embodiment 1:
[0034] Ball milling and mixing: Graphite tailings, coal gangue, potassium feldspar, air entraining agent, water reducing agent, talc and foaming agent CaCO3 are weighed in proportion, and the mass fraction of each raw material includes: 40 parts of graphite tailings, 48 parts of coal gangue, 10 parts of potassium feldspar, 1 part of air entraining agent, 1 part of water reducing agent and 10% of CaCO3. The ratio of material: ball = 1:2, material: water = 1:0.7 is put into a ball mill, and wet ball mill is carried out for 2 hours to obtain a mixed material;
[0035] Preparation of blanks: The mixed materials were dried at 110℃±5℃, dry-milled for 1h, and the obtained powders were sieved through a 200-mesh sieve to obtain the test powders;
[0036] Blank forming: dry forming method was adopted, and the obtained powder was pressed into a blank with a diameter of 3 cm at a pressure of 10 MPa using a tablet press;
[0037] Firing and foaming: Place the sample in a muffle furnace, heat it to 700°C at a rate of 5°C / min and keep it warm for 60 min. Open the furnace door and quickly place the green body in the muffle furnace. Then heat it to 900°C at a rate of 4°C / min and keep it warm for 60 min. After sintering, cool the sample to room temperature with the furnace.
[0038] The bulk density of the foamed ceramic obtained in this embodiment is 264 kg / m 3 , compressive strength 2.79MPa, flexural strength 0.59MPa, thermal conductivity 0.023W / (m·K), meeting the requirements of T / CBCSA 12-2019 "Foamed Ceramic Partition Board" for thermal insulation materials.
[0039] Embodiment 2:
[0040] Ball milling and mixing: Graphite tailings, coal gangue, potassium feldspar, air entraining agent, water reducing agent, talc and foaming agent CaCO3 are weighed in proportion, and the mass fraction of each raw material includes: 35 parts of graphite tailings, 46 parts of coal gangue, 10 parts of potassium feldspar, 2 parts of air entraining agent, 2 parts of water reducing agent, 5 parts of talc and 10% of CaCO3, and put them into a ball mill according to the ratio of material: ball = 1:2, material: water = 1:0.7, and wet ball mill for 2 hours to obtain a mixture;
[0041] Preparation of blanks: The mixed materials were dried at 110℃±5℃, dry-milled for 1h, and the obtained powders were sieved with 200 mesh to obtain the test powders;
[0042] Blank forming: dry forming method was adopted, and the obtained powder was pressed into a blank with a diameter of 3 cm at a pressure of 15 MPa using a tablet press;
[0043] Firing and foaming: Place the sample in a muffle furnace, heat it to 700°C at a rate of 5°C / min and keep it warm for 60 min. Open the furnace door and quickly place the green body in the muffle furnace. Then heat it to 900°C at a rate of 5°C / min and keep it warm for 60 min. After sintering, cool the sample to room temperature with the furnace.
[0044] The bulk density of the foamed ceramic obtained in this embodiment is 233 kg / m 3 , compressive strength 0.64MPa, flexural strength 0.43MPa, thermal conductivity 0.079W / (m·K), meeting the requirements of T / CBCSA12-2019 "Foamed Ceramic Partition Board" for thermal insulation materials.
[0045] Embodiment three:
[0046] Ball milling and mixing: Graphite tailings, coal gangue, potassium feldspar, air entraining agent, water reducing agent, talc and foaming agent CaCO3 are weighed in proportion, and the mass fraction of each raw material includes: 30 parts of graphite tailings, 44 parts of coal gangue, 10 parts of potassium feldspar, 3 parts of air entraining agent, 3 parts of water reducing agent, 10 parts of talc and 20% of CaCO3, and put them into a ball mill according to the ratio of material: ball = 1:2, material: water = 1:0.7, and wet ball mill for 2 hours to obtain a mixture;
[0047] Preparation of blanks: The mixed materials were dried at 110℃±5℃, dry-milled for 1h, and the obtained powders were sieved through a 200-mesh sieve to obtain the test powders;
[0048] Blank forming: dry forming method was adopted, and the obtained powder was pressed into a blank with a diameter of 3 cm at a pressure of 15 MPa using a tablet press;
[0049] Firing and foaming: Place the sample in a muffle furnace, heat it to 700°C at a rate of 5°C / min and keep it warm for 60 min. Open the furnace door and quickly place the green body in the muffle furnace. Then heat it to 920°C at a rate of 4°C / min and keep it warm for 60 min. After sintering, cool the sample to room temperature with the furnace.
[0050] After testing, the volume density of the foamed ceramic partition board obtained in this embodiment is 199kg / m 3 , compressive strength 0.53MPa, flexural strength 0.33MPa, thermal conductivity 0.072W / (m·K), meeting the requirements of GB / T33500-2017 "External Wall Insulation Foam Ceramics" and T / CBCSA 12-2019 "Foamed Ceramic Partition Boards" for thermal insulation materials.
[0051] Embodiment 4:
[0052] Ball milling and mixing: graphite tailings, coal gangue, potassium feldspar, air entraining agent, water reducing agent, talc and foaming agent CaCO3 are weighed in proportion, and the mass fraction of each raw material includes: 30 parts of graphite tailings, 40 parts of coal gangue, 10 parts of potassium feldspar, 5 parts of air entraining agent, 5 parts of water reducing agent, 10 parts of talc and 30% of CaCO3, and put them into a ball mill according to the ratio of material: ball = 1:2, material: water = 1:0.7, and wet ball mill for 2 hours to obtain a mixture;
[0053] Preparation of blanks: The mixed materials were dried at 110℃±5℃, dry-milled for 1h, and the obtained powders were sieved through a 200-mesh sieve to obtain the test powders;
[0054] Blank forming: dry forming method was adopted, and the obtained powder was pressed into a blank with a diameter of 3 cm at a pressure of 20 MPa using a tablet press;
[0055] Firing and foaming: Place the sample in a muffle furnace, heat it to 700°C at a rate of 5°C / min and keep it warm for 60 min. Open the furnace door and quickly place the green body in the muffle furnace. Then heat it to 950°C at a rate of 5°C / min and keep it warm for 60 min. After sintering, cool the sample to room temperature with the furnace.
[0056] After testing, the volume density of the foamed ceramic partition board obtained in this embodiment is 132kg / m 3, compressive strength 0.33MPa, flexural strength 0.16MPa, thermal conductivity 0.043W / (m·K), meeting the requirements of GB / T33500-2017 "External Wall Insulation Foam Ceramic" for thermal insulation materials.
[0057] It can be seen from the above embodiments that the foamed ceramic partition board prepared by the present invention has good performance, realizes the resource utilization of graphite tailings and coal gangue, and has important economic and environmental benefits.
[0058] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A method for preparing exterior wall thermal insulation foam ceramics using graphite tailings, characterized in that: The following steps are involved: Step 1: ball milling and mixing: graphite tailings, coal gangue, potassium feldspar, air entraining agent, water reducing agent, talc and foaming agent are weighed in proportion with CaCO3, and ball milled to obtain a mixture; Step 2: blank preparation: the mixed material is dried at 110℃±5℃, and then dry-milled to obtain each test powder; Step 3: Blank forming: using dry forming method, the obtained powder is pressed into shape; Step 4: Firing and foaming: Place in a muffle furnace and sinter at 950°C.
2. The method for preparing exterior wall thermal insulation foam ceramics using graphite tailings according to claim 1, characterized in that: In step 1, the mixture obtained by ball milling is put into a ball milling jar in a ratio of material: ball = 1:2, material: water = 1:0.7, and wet ball milling is performed for 2 hours to obtain the mixture.
3. The method for preparing exterior wall thermal insulation foam ceramics using graphite tailings according to claim 1, characterized in that: In step 1, the mass fractions of the raw materials include: 35-40 parts of graphite tailings, 40-48 parts of coal gangue, 10 parts of potassium feldspar, 1-5 parts of air entraining agent, 1-5 parts of water reducing agent, 5-10 parts of talc and 10%-30% of CaCO3.
4. The method for preparing exterior wall thermal insulation foam ceramics using graphite tailings according to claim 1, characterized in that: In step 1, dry ball mill is used for dry ball milling.
5. The method for preparing exterior wall thermal insulation foam ceramics using graphite tailings according to claim 4, characterized in that: Before the dry ball mill is put into operation, it is necessary to check whether all parts of the equipment are operating normally to ensure that there is no abnormality or failure in the equipment. After the dry ball mill is finished working, the unloading operation can only be carried out after the equipment is completely stopped. It is strictly forbidden to unload the dry ball mill when it is in working state.
6. The method for preparing exterior wall thermal insulation foam ceramics using graphite tailings according to claim 1, characterized in that: In step 2, the blank is prepared by dry ball milling for 1 hour, and the resulting powder is passed through a 100-mesh sieve.
7. The method for preparing exterior wall thermal insulation foam ceramics using graphite tailings according to claim 6, characterized in that: After the powder is sieved, the powder larger than 100 mesh is dry ball milled again until it meets the sieving requirements.
8. The method for preparing exterior wall thermal insulation foam ceramics using graphite tailings according to claim 1, characterized in that: In step 3, the blank is formed by pressing the obtained powder into a blank with a diameter of 3 cm at a pressure of 10-20 MPa using a tablet press.
9. The method for preparing exterior wall thermal insulation foam ceramics using graphite tailings according to claim 1, characterized in that: In step 3, after the blank is pressed and formed, it is necessary to protect the blank to prevent it from being hit, broken or crushed.
10. The method for preparing exterior wall thermal insulation foam ceramics using graphite tailings according to claim 1, characterized in that: In step 4, the firing system is as follows: first, the temperature is raised to 700°C at a rate of 5°C / min, the furnace door is opened and the green body is quickly placed in the muffle furnace, and then the temperature is raised to 950°C at a rate of 4-5°C / min and kept at this temperature for 60 minutes; After sintering, the sample was cooled to room temperature in the furnace.
Citation Information
Patent Citations
Foamed ceramic light inner wall board prepared from coal gangue and graphite tailings and preparation method
CN107352972A
Method for preparing light ceramic tile from graphite tailings
CN111205103A
Foamed ceramic based on graphite tailings and preparation method of foamed ceramic
CN112321319A
Foaming ceramic material based on graphite multi-source solid waste, preparation method of foaming ceramic material and partition board
CN114538951A
Foamed ceramic external wall thermal insulation material and preparation method thereof
CN116283342A
